2010
DOI: 10.1051/0004-6361/201013994
|View full text |Cite
|
Sign up to set email alerts
|

Puzzling asteroid 21 Lutetia: our knowledge prior to the Rosetta fly-by

Abstract: Aims. A wide observational campaign was carried out in [2004][2005][2006][2007][2008][2009] that aimed to complete the ground-based investigation of Lutetia prior to the Rosetta fly-by in July 2010. Methods. We obtained BVRI photometric and V-band polarimetric measurements over a wide range of phase angles, and visible and infrared spectra in the 0.4-2.4 μm range. We analyze them with previously published data to retrieve information about Lutetia's surface properties.Results. Values of lightcurve amplitudes, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
59
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 57 publications
9
59
0
Order By: Relevance
“…• 48 on 2008 November 30, which is consistent with the phase law deduced from visible observations (Belskaya et al 2010).…”
Section: Observations Data Reduction and Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…• 48 on 2008 November 30, which is consistent with the phase law deduced from visible observations (Belskaya et al 2010).…”
Section: Observations Data Reduction and Resultssupporting
confidence: 87%
“…Lutetia was extensively observed in the 1970s, yielding visible and near-IR reflectance spectra (McCord & Chapman 1975), radiometric albedos and diameter estimates (Morrison 1977), and polarimetric albedos and diameter estimates (Zellner & Gradie 1976), which have been confirmed by similar observations reported during the last decade (see Belskaya et al 2010). Based Fig.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Although we find an expressive phase bluing in the A 0 spectral slope map. Belskaya et al (2010) work on polarimetry of Lutetia was also inconclusive in respect to the existence of coherent-backscattering mechanism. Belskaya et al showed that Lutetia presents one of broadest negative polarization branch, only (234) Barbara and other four asteroids have wider negative polarization than Lutetia.…”
Section: Discussionmentioning
confidence: 99%